Assessment of two faecal sludge treatment plants in urban areas: Case study in Beijing - Shikun, Cheng; Lei, Zheng; Mingyue, Zhao; Xue, Bai; Zifu, Li; Mang, Heinz-Peter (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Every day, human beings produce excreta all over the world, and the sludge that accumulates in waste disposal systems is referred to as the ‘faecal sludge (FS)’. FS can cause serious environmental pollution in urban areas if it cannot be disposed of properly. A complete FS management system must include onsite sanitation technologies, FS collection and transport, a treatment plant, and resource recovery or disposal of the treatment end-products. Focusing on the treatment and reuse/disposal step of a FS complete service chain, this research presents two cases of FS treatment in Beijing. In Case 1, FS biogas plant adopts anaerobic digestion (AD) to treat FS, and the digestate can be used as biofertilizer in the surrounding greenhouse. In Case 2, several technologies including solid-liquid separation, dewatering, pyrolysis, AD and co-composting are integrated to find innovative solutions for FS treatment. A comprehensive assessment including the aspects of technology, economy and environment is conducted for further SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis. Then, critical strategies are developed, which include (1) selecting project site for optimized transportation, maximum waste reuse, minimum environmental impact and convenient final effluent disposal; (2) planning technical options at a feasible study stage, considering resource recovery, secondary pollution prevention and fire protection; (3) exploring market channels for by-products sale to increase profitability; (4) guaranteeing engineering quality and service life for the purpose of sustainable operation; (5) minimizing health risks to persons exposed to the untreated FS; and (6) providing necessary training for hygiene protection. The cases in Beijing can provide valuable lessons for urban areas in developing countries and the strategies can provide a reference for stakeholders and decision-makers who intend to develop FS treatment projects.Keywords: faecal sludge, kitchen waste, composting, anaerobic digestion, SWOTDOI: 10.3965/j.ijabe.20171003.3067Citation: Cheng S K, Zheng L, Zhao M Y, Bai X, Li Z F, Mang H P. Assessment of two faecal sludge treatment plants in urban areas: Case study in Beijing. Int J Agric & Biol Eng, 2017; 10(3): 237–245.